2013
DOI: 10.1093/infdis/jit007
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Brucellae Replicate in Human Trophoblasts

Abstract: Brucellae replicate in a vacuole derived from the endoplasmic reticulum (ER) in epithelial cells, macrophages, and dendritic cells. In animals, trophoblasts are also key cellular targets where brucellae efficiently replicate in association with the ER. Therefore, we investigated the ability of Brucella spp. to infect human trophoblasts using both immortalized and primary trophoblasts. Brucella extensively proliferated within different subpopulations of trophoblasts, suggesting that they constitute an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 31 publications
8
59
0
Order By: Relevance
“…By this way, Brucella reproduces within ER-derived compartments in both phagocytes (47,50,52), and in trophoblasts of infected animals (53)(54)(55)(56). A recent study showed that Brucella replicates in several human trophoblast subpopulations and can interfere with the invasive capacity of extravillous trophoblast-like cells (57). This novel replication profiles of Brucella in human trophoblasts give insights into the pathogenesis of infectious abortion (58).…”
Section: Abortionsmentioning
confidence: 99%
“…By this way, Brucella reproduces within ER-derived compartments in both phagocytes (47,50,52), and in trophoblasts of infected animals (53)(54)(55)(56). A recent study showed that Brucella replicates in several human trophoblast subpopulations and can interfere with the invasive capacity of extravillous trophoblast-like cells (57). This novel replication profiles of Brucella in human trophoblasts give insights into the pathogenesis of infectious abortion (58).…”
Section: Abortionsmentioning
confidence: 99%
“…replicate within an intracellular compartment that contains ER resident proteins, the molecular mechanisms by which the pathogen secures this replicative niche remain obscure (Qin et al 2008). Brucella replicate in a vacuole derived from the ER in epithelial cells, macrophages, and dendritic cells (Salcedo et al 2013). Thus far, factors that mediate Brucella infection of host cells remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated that Brucella replicates in several human trophoblast subpopulations and can interfere with the invasive capacity of extravillous trophoblast-like cells in vitro (7). In one of the largest series of pregnancies complicated with brucellosis, we have also showed that brucellosis in pregnancy is associated with increased incidence of spontaneous abortions not only in livestock but also in human pregnancies (8).…”
mentioning
confidence: 54%